Deliar Noer: Sebuah Biografi Politik, 1951-1999 - Maskur, Abu; Humaidi, Humaidi; Ibrahim, Nurzengky (Universitas Hamzanwadi, 2022)
In contemporary Indonesian politics in Islamic thought history, Deliar Noer cannot be passed over. He is a figure in Muslim Student Association (HMI), Masyumi, Academician, and a political figure who is a substantial thinker as well, proved by his academic works. As a political figure, his intellectuality is not only seen in his writings. Nevertheless, he attempted to make it through an established political party named Partai Ummat Islam. This study aims to examine the political role of Deliar Noer in political dynamics in Indonesia from 1951 to 1999. This study implied four stages of historical research methods. Those methods are heuristic, verification, interpretation, and historiography. The results of this study convey that Deliar Noer began his political experience when he took charge as the chief of the Muslim Student Association (HMI). Furthermore, he became a political observer, defended democracy, and established a political party.Dalam perpolitikan Indonesia kontemporer dalam sejarah pemikiran Islam, Deliar Noer tidak bisa dilewatkan begitu saja. Ia adalah tokoh Himpunan Mahasiswa Muslim (HMI), Masyumi, Akademisi, dan tokoh politik yang juga pemikir yang substansial, dibuktikan dengan karya-karya akademisnya. Sebagai seorang tokoh politik, intelektualitasnya tidak hanya terlihat pada tulisan-tulisannya. Meski demikian, ia berusaha melalui partai politik mapan bernama Partai Ummat Islam. Penelitian ini bertujuan untuk mengkaji peran politik Deliar Noer dalam dinamika politik di Indonesia dari tahun 1951-1999. Penelitian ini mengimplikasikan empat tahapan metode penelitian sejarah. Metode-metode tersebut adalah heuristik, verifikasi, interpretasi, dan historiografi. Hasil penelitian ini menyampaikan bahwa Deliar Noer memulai pengalaman politiknya saat menjabat sebagai Ketua Himpunan Mahasiswa Islam (HMI). Selanjutnya, ia menjadi pengamat politik, membela demokrasi, dan mendirikan partai politik.